2018
DOI: 10.1111/jcpt.12747
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K1 and Vitamin K2 immunopharmacological effects on the peripheral lymphocytes of healthy subjects and dialysis patients, as estimated by the lymphocyte immunosuppressant sensitivity test

Abstract: The present data suggest that VK2 has immunosuppressive efficacy. VK2 may enhance the immunosuppressive efficacies of glucocorticoids while preventing osteoporosis caused by glucocorticoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
(76 reference statements)
2
10
0
Order By: Relevance
“…Our previous studies highlighted the immunosuppressive effects of vitamins K2 and K3 (Hatanaka et al, 2014;Kusano et al, 2018;Meng et al, 2018;Xu, Meng, Wu, et al, 2019). In the present study, we compared the cytotoxic effects of vitamins K1, K2, and K3 on viabilities of T-cell mitogen-activated PBMCs (Figure 9 and Table 1).…”
Section: Discussionmentioning
confidence: 88%
“…Our previous studies highlighted the immunosuppressive effects of vitamins K2 and K3 (Hatanaka et al, 2014;Kusano et al, 2018;Meng et al, 2018;Xu, Meng, Wu, et al, 2019). In the present study, we compared the cytotoxic effects of vitamins K1, K2, and K3 on viabilities of T-cell mitogen-activated PBMCs (Figure 9 and Table 1).…”
Section: Discussionmentioning
confidence: 88%
“…Furthering this finding, K2 decreases proliferation of T-cells from healthy individuals, whereas vitamin K1 had no such effect [ 103 ]. This has been further substantiated with T-cells from a larger number of children with pediatric atopic dermatitis and healthy controls, as well as a separate study with patients on dialysis [ 104 , 105 ]. Both these studies demonstrated that K2 decreased the number of activated T-cells, as well as proliferation.…”
Section: Vitamin K2 In Health and Diseasementioning
confidence: 91%
“…The data were analyzed with FACSCanto II (BD Biosciences), using BD FACSDiva software. CD4 + T cells in the lymphocyte fraction were gated, and the percentages of CD4 + CD25 + and CD4 + CD25 + Foxp3 + cells in the CD4 + cell fraction were calculated, respectively, as we described previously (Kusano et al, 2018; Meng et al, 2018).…”
Section: Methodsmentioning
confidence: 99%